The Strategy of Principle Leadership in Elevating Teaching Learning Process in School - Agustina Setyaningsih; Yance Manoppo; Everhard Markiano Solissa; Najamuddin Petta Solong; Hendrajaya Hendrajaya (Journal on Education, 2023)
The purpose of this study was to analyze the principal's leadership strategy in improving school quality, to determine the impact of implementing the principal's leadership strategy in improving school quality and to analyze the supporting and inhibiting factors for the implementation of the principal's leadership strategy and program in improving school quality in one of the private school in West Java. This research uses qualitative research methods. The steps taken in this research process include (1) determining the type of data, (2) determining data sources, (3) determining data collection methods and techniques, (4) determining data analysis techniques, and (5) checking techniques for validity testing data. The time of this research was carried out for 3 months starting from the first week of August until the end of October 2022. Within 3 months the researchers hoped to be able to collect the data needed to answer the problems in this study. The school principal has created useful and effective programs and strategies to improve quality schools. The strategies that have been formulated by the school principal referring to situational leadership theory in the R4 Leadership model (delegating/observing) have gone well and been carried out effectively and efficiently and are very influential for improving the quality of schools. The implementation of these programs and strategies continues to be intensively improved by the school. The impact of implementing the principal's leadership strategy and program can be seen from the school's achievements, namely in the academic and non-academic fields. The principal as a manager is capable of managing his school by dividing tasks and authorities and involving all interested parties.